2021
DOI: 10.3390/nu13061792
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Health, Nutrition and Anthropometry in Professional Footballers: A Preliminary Study

Abstract: Poor oral health in elite sport is a pressing issue, however little is known about the periodontal status of professional footballers. The aim of this study was to examine the prevalence of periodontitis in a group of professional footballers and its association with nutritional parameters and self-report non-traumatic injuries. Additionally, we assessed its association with anthropometric, dietary inflammatory load and self-reported muscular and/or articular injuries. Twenty-two professional footballers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 33 publications
(42 reference statements)
3
18
0
1
Order By: Relevance
“…Moderately elevated periodontal pockets (PSI score 3: none above 5.5 mm) were assessed. This low severity is in line with a previous study on periodontitis in footballers that reported overall mild periodontitis and a similar prevalence of periodontitis [ 5 ]. Even though the extent of systemic changes depends on the severity of periodontitis [ 28 ], increased CRP values have also been stated due to experimental gingivitis caused by cessation of oral hygiene [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moderately elevated periodontal pockets (PSI score 3: none above 5.5 mm) were assessed. This low severity is in line with a previous study on periodontitis in footballers that reported overall mild periodontitis and a similar prevalence of periodontitis [ 5 ]. Even though the extent of systemic changes depends on the severity of periodontitis [ 28 ], increased CRP values have also been stated due to experimental gingivitis caused by cessation of oral hygiene [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of both gingivitis and periodontitis can be high [ 1 ] and differs significantly from non-elite controls [ 2 , 3 , 4 ]. For instance, among footballers, a periodontitis prevalence of 41% was reported [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the data report a significant treatment need to manage periodontal health. A detailed periodontal examination in footballers (mean age: 28 years) reported a similar prevalence of periodontitis (41%), with the diagnosis of a moderate or severe stage in only two individuals (9%) 19 …”
Section: Discussionmentioning
confidence: 91%
“…However, as previous studies have reported, athletes commonly have oral health problems: 13 About 46% have dental caries 14 with a higher prevalence than controls 15,16 . Gingival inflammation is very common with 58% to 85% 2–4,15,17,18 and even periodontitis is reported in 5% to 41% 3,4,17–19 . Erosion affects nearly every second athlete 20 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation